Доцільність застосування методу зворотного формування температурної нерівномірності для роз’ємних корпусів циліндрів парових турбін - Кнабе, О. Г.; Нечуйвітер, М. М.; Шелепов, І. Г. (НТУ "ХПІ", 2014)
У статті розглянута проблема енергетики України – підвищення економічності, маневреності, надійності електростанцій відносно продовження строку експлуатації теплоенергетичного встаткування енергетичних блоків (парових турбін), що перебувають в експлуатації, а також виявлення можливостей енергозберігаючих режимів з метою підвищення їх технічної ефективності. Визначено критерій забезпечення стабільності застосування методу зворотного формування температурної нерівномірності в пускових режимах парових турбін з різних теплових станів без обігріву фланців і шпильок і з обігрівом фланців і шпильок по відповідних програмах керування, а також його доцільність.

This paper deals with the problem related to the power engineering in Ukraine, in particular, an increase in the efficiency, maneuverability, and reliability of power stations with regard to the extension of the operation time of the thermal power equipment of operated power plants (steam turbines) and search for the opportunities of using energy saving modes to increase their technical efficiency. The control methods of the thermal state of steam turbines with supercritical and high parameters operated in start-up conditions have been analyzed. The application of the method of the reverse formation of temperature inhomogeneity by maintaining the density of the horizontal opening of external and internal cylinder bodies taking into consideration the operation of many units of the stream turbine that retard the speed of starting operations has been proposed. A criterion that provides a stable use of the method of inverse formation of the temperature inhomogeneity in starting modes of steam turbines using different thermal states with and/or without heating the flanges and pins and using also appropriate control programs has been defined and its appropriateness has been studied. The appropriateness of the use of the method of the inverse formation of temperature inhomogeneity for the split cylinder bodies of steam turbines has been determined.
Appropriateness of the use of the method of the inverse formation of temperature inhomogeineity for the split cylinder bodies of steam turbines
Keywords: розкриття горизонтальних роз’ємів; управління тепловим станом; пускова мобільність; steam turbine; steam turbine cylinder body; horizontal split opening; thermal state control; starting mobility